Attention, Music, Dance: Embodying the “Cinema of Attractions” (Sound Stage Screen, 2021)
In this essay I take up the question of whether the “cinema of attractions,” as identified and analyzed by film scholars Tom Gunning and André Gaudreault, might be a useful tool for critical analysis not only of early silent film, its exhibitionist aesthetics, and approach to spectatorship, but of theatrical dance from the period. Certainly, as for its general historical currency, the “cinema of attractions” is thought to encode the culture of modernity from which it arose: the visual spectacle, sensory fascination, bodily engagement, mechanical rhythm, violent juxtapositions, and new experiences of time and space available within the modern urban environment. Moreover, that cinema relied in no small part on dance itself: as a performing art, dance was central to the “attractions” industry, prime raw material starring The Body in Motion, a favorite fascination of contemporary art and popular entertainment. My aim is to push the analogy further, suggesting how cinema and theatrical dance might cue a similar mode of attention: that is, despite the former’s reliance on the camera, its reproductive aesthetic and industrial mechanicity, and the latter’s live theatrical aspect. Indeed, in the latter, I argue, music can be analogized to the camera itself, helping determine and sustain a particular attention economy, while pointing to itself—just as filmed objects stare at the camera—as artifice or contrivance.
Keywords: Attention; Dance; The Rite of Spring; Loie Fuller; haptics